ANALISIS TEGANGAN DAN PENYEBAB PENURUNAN KEKERASAN PADA BRACKET ARM LINK DENGAN MATERIAL ALUMINIUM 7050 T4751 - Zainuddin, Zainuddin; Aminudin, Muhammad; Ismantoro, Ardian; Burhanudin, Burhanudin (Teknika, 2024)
In aviation, security and safety are the main priorities, so the components' quality must meet specified standards. One of the components that will be discussed is the arm link bracket located on the wing or left wing of the aircraft, which functions as a support fixture for the arm link. This component is made from Aluminum 7050 T7451 material. In this case, a decrease in the hardness value of Aluminum 7050 T7451 was found to be 80 HB from the standard 82–92 HB, which is feared to be a problem in the future. So, it is necessary to find out the cause so that similar incidents can be avoided. The method used to analyze the leading causes of the decrease in the hardness value of Aluminum 7050 T7451 is by studying literature related to things that allow a reduction in material hardness and using the help of CAD/CAE software for Finite Element Analysis (FEA). The results obtained from the cause of the decrease in hardness of the Aluminum 7050 T7451 material are heat exposure, which is the only heat source based on sheet processing, and heat exposure occurs more than once. In addition, the thermal simulation results show that the heat exposure area spreads evenly across all parts in one exposure. The specific cause cannot yet be known, considering that the heat source of the machining process has many factors, such as the condition of the coolant, the condition of the cutter tools, and the unknown feed speed. In this case, the simulation results show that the maximum stress of 259.6 MPa is still in the safe category with a safety factor value of 1.491.